The Training Needs of the First Three Grades Teachers in The Rusaifa District Schools to Employ the Principles of UDL from Their Point of View - Alnawasrah, Andaleeb Ibrahim Sadeq (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of the training needs of the first three grades teachers in the Rusaifa district education directorate to employ the principles of UDL from their point of view, the study used the descriptive analysis approach, questionnaire has been used it consisted from (17) paragraph, the sample of study consisted from (150) female and male teachers. However, the finding of study showed that the degree of the training needs of the first three grades teachers in the Rusaifa district education directorate to employ the principles of UDL from their point of view was High with average (3.74. out of 5) at the domain level; The needs of educational materials got the highest average (3.79 out of 5), then the needs of teaching strategies with an average (3.73 out of 5), and the needs of the reality of the application of design and design principles were equal with an average of (3.71 out of 5) for each, and all of them had a degree of need (high). The finding also showed there were a significant difference at (α ≤ 0.05) in the degree the training needs of the first three grades teachers in the Rusaifa district education directorate to employ the principles of UDL from their point of view refers to variable of teacher’s years of experience in favor of less than 10 years. Furthermore, there weren’t any significant differences according to teacher qualification. Based on the results, the researcher recommended including the principles of comprehensive design for learning in programs Qualifying pre-service teachers and, in the curricula, and that professional development programs for teachers focus on preparing educational materials in accordance with the principles of comprehensive design for learning and measuring their impact on learners, as suggested by complementary studies on the subject.